PROPOSAL FOR OEE (OVERALL EQUIPMENT EFFECTIVENESS) INDICATOR DEPLOYMENT IN A BEVERAGE PLANT - Araujo, Fernando Oliveira de; Castro, Fabiana Pereira (Brazilian Journal of Operations & Production Management, 2013)
The tough competitiveness seen in the beverage industry, especially in emerging segments like isotonic drinks and iced teas, requires companies to seek competitive advantages to stay or increase their participation in the consumer market. In this sense reducing wastes and assuring compliance in production process are identified as key variables in this industry. This work presents the application of the OEE (Overall Equipment Effectiveness) methodology in the production line of a company which fills beverage in PET bottles, in order to assess the plant operational performance. In this direction primary data were collected and the line downtimes were stratified, and the indicators used by the plant were confronted with the dimensions that make up the OEE indicator (Availability, Performance and Quality) in order to assess the possible behaviors and correlations. As a result, it was noted that the longest downtimes were caused by downtimes of the inkjet printer and the filler, and there was a strong correlation between the indices of the OEE and the existing indicators in the plant despite the bias (ε).